Management strategies for Cytospora plurivora: the role of canopy sprays in western Colorado peach orchards - Greenberger, Jilly Sal, author; Stewart, Jane E., advisor; Tonnessen, Bradley W., committee member; Charkowski, Amy, committee member; Uchanski, Mark, committee member (Colorado State University. Libraries, 2024)
Cytospora spp. are globally distributed pathogens on more than 120 species of woody plants, in both agricultural and natural systems. In Colorado, Cytospora canker, primarily caused by the fungal pathogen Cytospora plurivora, is one of the most destructive diseases affecting peach trees (Prunus persica), a key specialty crop with significant economic and cultural importance. The resulting yield loss and financial strain on peach growers threaten the survival of the industry and options for management are limited. No resistant varieties have been identified and no fungicides are currently registered for use on Cytospora canker in Colorado. Chemical management focuses on prevention of new infections on wounded tissue: the infection court for C. plurivora. Fungicides applied directly to pruning wounds have proven effective but are impractical for many growers due to the extensive labor required. Additionally, these spot treatments have not been evaluated for efficacy on wounds on main scaffold branches or trunks, which are critical infection sites. Canopy sprays, facilitated by air-blast sprayers, could be a more cost-effective option for Cytospora canker control, with the potential to target entire tree scaffolds. Air blast sprayers are currently used by growers to manage other diseases and pests, as well as for nutrient applications; however, their efficacy on canker pathogens is not well understood. This study aims to explore the utility of canopy sprays with air blast sprayers for management of C. plurivora in organic and conventional peach orchards, and to determine best practices for achieving optimum coverage of bark on scaffold branches. Field trials were conducted in organic and conventional orchards, located at the CSU Agricultural Experiment stations in western Colorado, to assess both spray coverage and fungicide efficacy. Field trials to assess air-blast spray coverage were conducted in the spring and summer of 2023 to explore the effect of season of application and fan use on bark coverage. Water Sensitive Paper (WSP) cards were placed at three heights on each tree, sprayed with water, and analyzed with ImageJ software (Rasband, 1997) to determine the percent coverage of cards. Higher percent coverage was observed in the spring on bare trees, likely due to foliage blocking cards in summer trials. Fan use had variable effects on coverage within and between orchard planting blocks. Issues with uniformity in coverage were observed in all orchard blocks, with top cards receiving the lowest coverage in almost all cases. Fungicide field trials were conducted in the fall of 2023 and spring of 2024. An Organic Materials Review Institute (OMRI) listed fungicide, lime sulfur (Lime-Sulfur Solution™, NovaSource), was tested in the organic orchard and a conventional fungicide, captan (Captan 4L, Drexel Chemical Company, Memphis, TN), tested in the conventional orchards. Trees were wounded and inoculated with mycelial plugs of C. plurivora at the bottom of primary scaffold branches, on mid-scaffold branches, and on top branches. Resulting lesions were measured several months post-inoculation to assess disease development. Fungicide efficacy was evaluated by comparing lesion area (mm2) of treated and untreated trees. In fall fungicide trials, minimal lesion growth was observed overall, and treatments with lime sulfur and captan showed no efficacy in any orchard planting block. In the spring fungicide trials, treatment with lime sulfur significantly decreased lesion size in the organic orchard: on middle branches by 58% and top branches by 87%. Results of captan treatments were inconclusive but warrant future studies. No efficacy was observed in one planting block in the conventional orchard, but in the planting block with more mature trees, captan treatment was associated with a 147% decrease in lesion size. The results of this study suggest that air blast sprayers may be an effective tool for C. plurivora management, but future studies are needed to confirm the extent of their efficacy. Fall canopy sprays may not be effective or necessary, while summer sprays may have limited efficacy due to low coverage on foliated trees. Efficacy was observed with spring application of lime sulfur at 3%, supporting its use in canopy sprays. Efficacy of captan applications could not be confirmed or rejected due to inconsistency of results. The rate used in this study, 3.5 liters/hectare, may be insufficient, as had been found previously. Midrate applications (7 liters/hectare) of captan should be tested in future studies. Overall, efficacy was limited, highlighting the importance of integrated pest management strategies and the need for continued research on alternatives to chemical control.
Keywords: canopy sprays; Cytospora plurivora; peach trees; Cytospora canker; canker pathogens; Leucostoma